Hereditary Breast Cancer in the Brazilian State of Ceará (The CHANCE Cohort): Higher-Than-Expected Prevalence of Recurrent Germline Pathogenic Variants - Gifoni, Ana Carolina Leite Vieira Costa; Gifoni, Markus Andret Cavalcante; Wotroba, Camila Martins; Palmero, Edenir Inez; Costa, Eduardo Leite Vieira; dos Santos, Wellington; Achatz, Maria Isabel (Frontiers in Oncology, 2022)
Purpose: There is a significant paucity of epidemiological data on hereditary cancer in Northeast Brazil. This is the largest study on the prevalence and mutation spectrum of cancer predisposition genes in the State of Ceará. Methods: Patients ≥18 years of age that were referred to CHANCE (Grupo de Câncer Hereditário do Ceará) from March 2014 to December 2020 with testing criteria for breast cancer susceptibility genes according to NCCN v.1.2021 were eligible to participate. The inclusion of patients was limited to one individual per family and to those born in the State of Ceará. All patients underwent a hereditary cancer panel testing with at least 30 genes. Results: The study included 355 patients, and 97 (27.3%) carried a P/LP germline variant in 18 different genes including high penetrant breast cancer genes - BRCA1 (31, 8.7%), BRCA2 (25, 7.0%), PALB2 (10, 2.8%) and TP53 (1, 0.28%); moderate-penetrant breast cancer genes - CHEK2 (7, 1.9%), ATM (4, 1.1%), BARD1 (2, 0.56%), RAD51C (1, 0.28%) and RAD51D (1, 0.28%); and genes without an established association with breast cancer predisposition (15, 4.2%): PMS2 (4, 1.1%), MUTYH (3, 0.8%), MEN1 (2, 0.56%), NTHL1 (1, 0.28%), RAD50 (1, 0.28%), SDHA (1, 0.28%), SUFU (1, 0.28%), DICER1 (1, 0.28%) and BLM1 (1, 0.28%). Among the 97 P/LP carriers, BRCA1 (31, 31.9%) and BRCA2 (25, 25.7%) were the most frequently mutated genes, followed by PALB2 (10, 10.3%), CHEK2 (7, 7.2%) and ATM (4, 4.1%). A small number of recurrent variants (detected in three or more individuals) represented the majority of the P/LP variants described in this cohort. There was no statistically significant association between any of the specific NCCN criteria scenarios and the detection of a P/LP variant. Conclusion: This study reinforces the importance of characterizing the mutational profile of cancer predisposition genes in diverse populations. This knowledge may contribute to better public policy choices and to a better clinical management.